Prevelence of Multivessel Anatomy in Primary Percutaneous Coronary Intervention (PCI) after Acute ST Elevation Myocardial Infarction - Vickee Kumar Mamtani, Naveed Ahmed Shaikh, Javed Khurshed Shaikh, Mir Fahad Hussain Talpur, Shahbaz Ali Shah, Rajesh Kumar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study aims to determine the frequency of multivessel anatomy in patients with Primary Percutaneous Coronary Intervention (PPCI) after Acute ST-Elevation Myocardial Infarction (STEMI). Methodology: From February 2017 to August 2017, this descriptive cross-sectional study was conducted in National Institute of Cardiovascular Diseases Karachi. P-value<0.05 was considered statistically significant. Patients of Either gender, having comorbid of Diabetic, hypertensive, obese, smokers or ex-smokers, from age ≥35 years and ≤65 years were included for the research subject. However, patients with a previous history of coronary angioplasty or thrombolytic therapy, valvular heart disease, CABG, and all those patients with non-ST-elevation myocardial infarction (NSTEMI) do not meet the criteria for STEMI on electrocardiography were excluded. Result: A total of 97 patients were evaluated with a mean age of 52.5 and standard deviation ±9.76 and weight mean was 68.65±10.86. A significant result was observed with the help of chi-square t-test analysis in the stratification for MVDA. Age was proportionally related to MVDA with a p-value of 0.001. Diabetes Mellitus is another significant factor in association with MVDA with a p-value of 0.001. Hypertension and current smoking status in association with multivessel disease reflect moderate evident significance while gender and ex smoking status have no association with MVDA. Conclusion: Patients with multi-vessel disease comprise the majority of patients undergoing PCI today and will likely remain so. With improved techniques, stents, and adjunctive drugs, outcomes have improved significantly